The factors of financial report transparency in the regional government - Sumartono, Sumartono; Pasolo, Muhammad Ridhwansyah (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2019)
This research is aimed at investigating the empirical factors affecting the financial report transparency in the regional government of Papua province. The quantitative approach was used in this research. 92 comprehensive questionnaires were analyzed quantitatively. The double linear regression analysis shows that the financial report presentation, accessibility, and internal control significantly affect the financial report transparency in the regional government. This research implies important contribution that the empirical findings of the effect of financial report presentation, accessibility, and internal control system on the financial report transparency in the regional government are expected to foster constructive recommendations in the form of policy related to the financial report transparency in the regional government.